کلاسیکی اُردو شاعر ی کا فنّی ارتقاء : ایک تجزیاتی مطالعہ: Artistic Evolution of Classical Urdu Poetry: An Analytical Study - Ahmad, Dr. Irshad; Asghar, Dr. Ghulam; Mahmood, Dr. Khalid (Al-Amīr Research Journal for Islamic Studies, 2024)
The classical era of Urdu poetry begins with the thirteenth century. Any language has to go a long way from dialect to literary creation. During this journey, it has to go through a number of grammatical and syntactic changes. When a dialect reaches the stage of its next advanced form, i.e. “language”, it makes its first creative expression in the form of poetry. The Urdu language also began its aesthetic expression, i.e. poetry, in the form of "Rekhta", the first painter of which was Amir Khosrow.When this Rekhta “entered its epoch in the eighteenth century through eloquence and simplicity; it met master poets like Mir Taqi Mir, Khawaja Mir Dard and Mirza Rafi-ud-Din Soda who added more color to its blood and liver. An analytical study of the literal, semantic and stylistic changes that took place during this evolutionary course of Urdu poetry from "Rekhta"to"Ahad-e-zarrin" will be discussed in this article. Keywords: classical era, Urdu poetry, artistic evolution, Eighteenth century